1997
DOI: 10.1177/00220345970760061001
|View full text |Cite
|
Sign up to set email alerts
|

Why do Shear Bond Tests Pull Out Dentin?

Abstract: It is widely accepted that a dentin shear bond test which pulls out dentin must mean that the adhesive strength is superior to the cohesive strength of the dentin. Using numerical modeling techniques, Van Noort et al. (1988, 1989) and DeHoff et al. (1995) alerted the scientific community that there were massive stress concentrations in the familiar dentin bond test. It is not inconceivable that these localized high tensile stresses could initiate cracks which diverge monolithically into dentin, leaving the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
159
1
26

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(190 citation statements)
references
References 13 publications
4
159
1
26
Order By: Relevance
“…In general, it is known that in the presence of strong bonds, the fracture path starts in resin composite propagating across the adhesive joint and then into dentin. 38 This suggests that the quality of the bond between the materials present at the interface is such that it surpasses the cohesive strength of its individual components and the adhesive strength between the interfacial layers, yielding an adhesive interfacial assembly that exhibits greater strength when acting as a single body rather than as separate layers. Moreover, the reported fracture modes may only be considered ''apparent'' as confirmation of ''true'' failure modes would require the use of sophisticated surface chemistry analysis instead of only high-magnification microscopic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it is known that in the presence of strong bonds, the fracture path starts in resin composite propagating across the adhesive joint and then into dentin. 38 This suggests that the quality of the bond between the materials present at the interface is such that it surpasses the cohesive strength of its individual components and the adhesive strength between the interfacial layers, yielding an adhesive interfacial assembly that exhibits greater strength when acting as a single body rather than as separate layers. Moreover, the reported fracture modes may only be considered ''apparent'' as confirmation of ''true'' failure modes would require the use of sophisticated surface chemistry analysis instead of only high-magnification microscopic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…7,12 Testing in shear mode is a relatively simple, reproducible and widely accepted test. [13][14][15] Although this mode of testing has been met with some criticism, it is still being used to evaluate the bonding potential of adhesives to dental structure. 12,16 The test may be particularly appropriate for testing glass ionomer cements, which present relatively low bond strengths and may not be suitable for other testing methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…Finite element analysis has been used to describe the distribution of interfacial shear stresses 5,8,9,13) . From these it appears that the interfacial shear stresses are highly non-uniform and strongly influenced by bonding geometry, loading conditions and the mismatch in elasticity among the bonded layers.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…It has been shown that the stress distribution in the dentin-adhesive interface is far from homogeneous 5,7,8) . Therefore, not only a possible change in material properties but also the mechanics of the shear test set-up could initiate monolithic fracture in the dentin, leading to cohesive failure 9) . To reduce bending moment, single plane slip shear bond testing is proposed by Watanabe 10) .…”
Section: ⅰ Introductionmentioning
confidence: 99%